solve for X in the equation

x/2 + x/6 = 2

First, you want to find a common denominator for the fractions on the left side of the equation so you can add those fractions. Since 6 is the smallest common denominator, multiply the first fraction by 3/3 to get a 6 in the denominator. That is, multiply x/2 by 3/3:

(x/2) · (3/3) = (x · 3)/(2 · 3) = 3x/6

Replace x/2 in the original equation by 3x/6:

3x/6 + x/6 = 2

Since you now have a common denominator, you can add the two fractions on the left side of the equation:

(3x + x)/6 = 2

After combining like terms, you end up at the following:

4x/6 = 2

Multiply both sides of the equation by 6:

6 · (4x/6) = 2 · 6

4x = 12

Divide both sides of the equation by 4:

(4x) / 4 = 12 / 4

x = 3

## Comments

Nice answer.